FAMILY FINANCIAL LITERACY OUTREACH PROGRAM AT SDI KHAZANAH KEBAJIKAN - Romantica, Krishna Prafidya; Septiarini, Tri Wijayanti; Husni Johan, Arsyelina; Putri Martinasari, Made Diyah; Andriani, Rosa; Iriani Tarigan, Asmara; Kurniawan, Heri (Jurnal Pengabdian Masyarakat Sabangka, 2025)
Financial literacy is a crucial element in raising public awareness regarding financial management. It is closely linked to financial planning, with family financial planning being a key aspect of financial management, specifically in creating a monthly budget. According to the 2024 OJK survey, the financial literacy index for women (66.75%) is higher compared to men (64.14%). Based on these findings, the outreach team from the Mathematics Study Program at Universitas Terbuka aims to support OJK's efforts to improve family financial literacy among female parents at SDI Khazanah Kebajikan. The program implementation is divided into three phases: preparation (where the outreach team conducts a direct visit to the school), execution, and evaluation (via a partner satisfaction survey). The survey results reveal that participants were highly satisfied with the program, with a satisfaction rate of 95%. This satisfaction was attributed to various factors, including the speaker's knowledge, the perceived benefits of the program, the relevance of the topics presented by the outreach team in line with their expertise, the program's ability to address current issues, and the clarity with which the material was delivered.